Uterine cancer after risk-reducing salpingo-oophorectomy without hysterectomy in women with BRCA mutations - Shu, Catherine A. (JAMA Oncol, 2016)
IMPORTANCE: The link between BRCA mutations and uterine cancer is unclear. Therefore, although risk-reducing salpingo-oophorectomy (RRSO) is standard treatment among women with BRCA mutations (BRCA+ women), the role of concomitant hysterectomy is controversial. OBJECTIVE: To determine the risk for uterine cancer and distribution of specific histologic subtypes in BRCA+ women after RRSO without hysterectomy. DESIGN, SETTING, AND PARTICIPANTS: This multicenter prospective cohort study included 1083 women with a deleterious BRCA1 or BRCA2 mutation identified from January 1, 1995, to December 31, 2011, at 9 academic medical centers in the United States and the United Kingdom who underwent RRSO without a prior or concomitant hysterectomy. Of these, 627 participants were BRCA1+; 453, BRCA2+; and 3, both. Participants were prospectively followed up for a median 5.1 (interquartile range [IQR], 3.0–8.4) years after ascertainment, BRCA testing, or RRSO (whichever occurred last). Follow up data available through October 14, 2014, were included in the analyses. Censoring occurred at uterine cancer diagnosis, hysterectomy, last follow-up, or death. New cancers were categorized by histologic subtype, and available tumors were analyzed for loss of the wild-type BRCA gene and/or protein expression. MAIN OUTCOMES AND MEASURES: Incidence of uterine corpus cancer in BRCA+ women who underwent RRSO without hysterectomy compared with rates expected from the Surveillance, Epidemiology, and End Results database. RESULTS: Among the 1083 women women who underwent RRSO without hysterectomy at a median age 45.6 (IQR: 40.9 – 52.5), 8 incident uterine cancers were observed (4.3 expected; observed to expected [O:E] ratio, 1.9; 95% CI, 0.8–3.7; P = .09). No increased risk for endometrioid endometrial carcinoma or sarcoma was found after stratifying by subtype. Five serous and/or serous-like (serous/serous-like) endometrial carcinomas were observed (4 BRCA1+ and 1 BRCA2+) 7.2 to 12.9 years after RRSO (BRCA1: 0.18 expected [O:E ratio, 22.2; 95% CI, 6.1–56.9; P < .001]; BRCA2: 0.16 expected [O:E ratio, 6.4; 95% CI, 0.2–35.5; P = .15]). Tumor analyses confirmed loss of the wild-type BRCA1 gene and/or protein expression in all 3 available serous/serous-like BRCA1+ tumors. CONCLUSIONS AND RELEVANCE: Although the overall risk for uterine cancer after RRSO was not increased, the risk for serous/serous-like endometrial carcinoma was increased in BRCA1+ women. This risk should be considered when discussing the advantages and risks of hysterectomy at the time of RRSO in BRCA1+ women.